2023
DOI: 10.3390/ijms241511908
|View full text |Cite
|
Sign up to set email alerts
|

Conservation of Markers and Stemness in Adipose Stem and Progenitor Cells between Cattle and Other Species

Abstract: Adipose stem and progenitor cells (ASPCs) have been isolated from humans and animals for use in regenerative medicine and therapy. However, knowledge of ASPCs in other species is limited. Particularly, ASPCs in livestock are expected to enhance the fat content and meat composition. In this study, we isolated bovine ASPCs using cell surface markers. Specifically, we focused on ASPC markers in humans and experimental animals, namely CD26, CD146, and CD54. Stromal vascular fraction cells from bovine fat were sepa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 24 publications
(41 reference statements)
0
1
0
Order By: Relevance
“…Disparities in adipogenesis between beef cattle's intramuscular and subcutaneous adipose progenitors have been documented [24,25]. The study of bovine adipose stem and progenitor cells revealed that preadipocytes can be collected and characterized as CD26−CD146+CD54+ or CD26−CD146+CD54− [26]. Song et al reported that porcine ADSCs could be differentiated into adipocytes using insulin, dexamethasone, IBMX, and rosiglitazone [27].…”
Section: Introductionmentioning
confidence: 99%
“…Disparities in adipogenesis between beef cattle's intramuscular and subcutaneous adipose progenitors have been documented [24,25]. The study of bovine adipose stem and progenitor cells revealed that preadipocytes can be collected and characterized as CD26−CD146+CD54+ or CD26−CD146+CD54− [26]. Song et al reported that porcine ADSCs could be differentiated into adipocytes using insulin, dexamethasone, IBMX, and rosiglitazone [27].…”
Section: Introductionmentioning
confidence: 99%
“…Pulmonary toxicity is a recognized adverse effect of anticancers, nevertheless, a mortality rate of 1%–4% from bleomycin is considered unacceptable for patients with treatable malignancies. The toxic effects of bleomycin are primarily caused by the generation of free radical and its lung specificity caused by bleomycin catalyzing hydrolase, which was not found in lung tissue, rendering this organ vulnerable to bleomycin toxicity ( Usman et al, 2010 ; Ishida et al, 2023 ).…”
Section: Introductionmentioning
confidence: 99%